The Global Effect of the COVID-19 Pandemic on STEMI Care: A Systematic Review and Meta-analysis - Chew, Nicholas W.S.; Ow, Zachariah Gene Wing; Teo, Vanessa Xin Yi; Heng, Ryan Rui Yang; Ng, Cheng Han; Lee, Chi-Hang; Low, Adrian F.; Chan, Mark Yan-Yee; Yeo, Tiong-Cheng; Tan, Huay-Cheem; Loh, Poay-Huan (Canadian journal of cardiology, 2021)
The COVID-19 pandemic has affected patients with ST-segment elevation myocardial infarction (STEMI) requiring primary percutaneous coronary intervention (PCI) worldwide. In this review we examine the global effect of the COVID-19 pandemic on incidence of STEMI admissions, and relationship between the pandemic and door to balloon time (D2B), all-cause mortality, and other secondary STEMI outcomes. We performed a systematic review and meta-analysis to primarily compare D2B time and in-hospital mortality of STEMI patients who underwent primary PCI during and before the pandemic. Subgroup analyses were performed to investigate the influence of geographical region and income status of a country on STEMI care. An online database search included studies that compared the aforementioned outcomes of STEMI patients during and before the pandemic. In total, 32 articles were analyzed. Overall, 19,140 and 68,662 STEMI patients underwent primary PCI during and before the pandemic, respectively. Significant delay in D2B was observed during the pandemic (weighted mean difference, 8.10 minutes; 95% confidence interval [CI], 3.90-12.30 minutes; P = 0.0002; I2 = 90%). In-hospital mortality was higher during the pandemic (odds ratio [OR], 1.27; 95% CI, 1.09-1.49; P = 0.002; I2 = 36%), however this varied with factors such as geographical location and income status of a country. Subgroup analysis showed that low–middle-income countries observed a higher rate of mortality during the pandemic (OR, 1.52; 95% CI, 1.13-2.05; P = 0.006), with a similar but insignificant trend seen among the high income countries (OR, 1.17; 95% CI, 0.95-1.44; P = 0.13). The COVID-19 pandemic is associated with worse STEMI performance metrics and clinical outcome, particularly in the Eastern low–middle-income status countries. Better strategies are needed to address these global trends in STEMI care during the pandemic. Dans le monde entier, la pandémie de COVID-19 a nui aux patients atteints d'infarctus du myocarde avec élévation du segment ST (STEMI) qui avaient besoin d'une intervention coronarienne percutanée (ICP) primaire. Dans cette revue, nous examinons les répercussions de la pandémie de COVID-19 à l’échelle mondiale sur le nombre d'admissions en raison de STEMI, et la relation entre la pandémie et le délai de prise en charge médicale aux urgences (D2B, de l'anglais door to balloon time), la mortalité toutes causes confondues et les autres critères secondaires liés au STEMI. Nous avons réalisé une revue systématique et une méta-analyse principalement pour comparer le D2B et la mortalité intrahospitalière des patients atteints d'un STEMI qui avaient subi une ICP primaire durant et avant la pandémie. Nous avons réalisé des analyses en sous-groupes pour examiner l'influence de la région géographique et du revenu des pays sur les soins aux patients atteints d'un STEMI. La consultation en ligne de bases de données consistait à trouver des études qui portaient sur la comparaison des critères liés au STEMI ci-dessus mentionnés durant et avant la pandémie. Au total, nous avons analysé 32 articles. Dans l'ensemble, 19 140 et 68 662 patients atteints d'un STEMI avaient subi une ICP primaire durant et avant la pandémie, et ce, de façon respective. Nous avons observé un D2B important durant la pandémie (différence moyenne pondérée, 8,10 minutes; intervalle de confiance [IC] à 95 %, 3,90-12,30 minutes; P = 0,0002; I2 = 90 %). La mortalité intrahospitalière était plus élevée durant la pandémie (ratio d'incidence approché [RIA], 1,27; IC à 95 %, 1,09-1,49; P = 0,002; I2 = 36 %). Toutefois, elle variait en fonction de facteurs tels que la région géographique et le revenu des pays. L'analyse en sous-groupes a montré que les pays à revenu faible ou intermédiaire avaient un taux plus élevé de mortalité durant la pandémie (RIA, 1,52; IC à 95 %, 1,13-2,05; P = 0,006), ainsi qu'une tendance similaire, mais non significative dans les pays à revenu élevé (RIA, 1,17; IC à 95 %, 0,95-1,44; P = 0,13). La pandémie de COVID-19 est associée à des indicateurs de performance et des issues cliniques liées aux STEMI qui sont pires, particulièrement dans les pays de l'Est à revenu faible ou intermédiaire. De meilleures stratégies sont nécessaires pour remédier à ces tendances mondiales dans les soins aux patients atteints d'un STEMI durant la pandémie.